Ambulatory blood pressure in hypertensive patients with autosomal dominant polycystic kidney disease - Li Kam Wa, T C; Macnicol, A M; Watson, M L (Nephrology, dialysis, transplantation, 1997)
Ambulatory blood pressure is more closely correlated with various indices of hypertensive target-organ damage, and is a better prognostic predictor of cardiovascular morbidity and mortality than conventional methods of blood pressure measurement. Autosomal dominant polycystic kidney disease (ADPKD) is complicated by hypertension, progressive renal failure, and an increased risk of cardiovascular mortality. This study investigated the 24-h ambulatory blood pressure profile in patients with ADPKD in view of the sparsity of such data in these patients and the possibility that abnormal diurnal blood pressure variations may have prognostic consequences. Ambulatory blood pressure was measured over a 24-h period by the oscillometric method with an automatic non-invasive recorder (SpaceLabs 90207 system) in matched groups of 25 hypertensive patients with ADPKD and 25 patients with essential hypertension. Both groups showed a nocturnal decrease in blood pressure, but this was significantly smaller in patients with ADPKD. There was no evidence of enhanced lability of blood pressure in ADPKD. The nocturnal fall in blood pressure was attenuated in patients with ADPKD. Further studies are required to assess the importance of this finding and its possible contribution to the progression of renal failure or increased cardiovascular mortality in these patients.